PENGARUH VARIASI KETEBALAN PCM TERHADAP KINERJA PEMANAS AIR TENAGA MATAHARI TERMOSIFON - Syahruddin, A. Syahrinaldy (Nusantara Hasana Journal, 2026)
Solar water heater technology is increasingly in demand by the wider community, this has led to an increasing number of research related to solar water heaters. The working efficiency of a thermosyphon solar water heater with the integration of heat storage materials is presented in this study. Heat absorbing collectors with varying thicknesses of paraffin wax PCM as the heat storage material are modeled and then the performance calculated theoritically. The variations thickness of the heat storage material are 6 mm, 10 mm, and 15 mm, respectively. The theoritically calculation conducted based on experimental data collection with varying constant solar radiation. The results of this study show that the working efficiency of the heat absorbing collector with a PCM thickness of 15 mm is greater when compared to thicknesses of 10 mm and 6 mm or collectors without heat storage material with an average efficiency of 67.49%.